PENGARUH FINANCIAL LITERACY, LIFE STYLE, LOCUS OF CONTROL DAN DEMOGRAFI TERHADAP PERILAKU KONSUMTIF GENERASI MILENIAL DI KOTA SUBANG - Dilasari Dilasari; Sri Mulyati; Asep Kurniawan (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
This study aims to determine the effect of financial Literacy, Life style, Locus of control and demographics on the consumption behavior of millennial generation in the city of Subang. Consumptive behavior is an action that prioritizes desires rather than needs, therefore consumption activities are actions taken to meet needs, if consumption is excessive, a consumptive behavior will occur.This research was conducted to the millennial generation in the city of Subang, aged 20 - 35 years in 2020. The method used in this study is a quantitative method. The number of samples in this study were 200 people, sampling using nonprobability sampling techniques with a purposive sampling approach. The data analysis technique used in this study is multiple linear regression analysis. The results of this study conclude that simultaneous financial literacy, life style, locus of control, and demographics influence the consumptive behavior of millennials in Subang City, Whereas according to the results of the hypothesis partially financial literacy variables, life style, positive and significant influence on consumptive behavior of millennial generation in Subang, locus of control variables have a negative and significant effect on consumptive behavior of millennial generation in Subang, while demographic variables (gender), and demographic (income) does not affect the consumption behavior of millennial generation in the city of Subang.